Analysis of Disaster’s and its Management Using Big Data Analytics - Mishra, Nirbhay; Singh, Dharmpal; Majumdar, Amit; Nag, Shinjini; Gupta, Manish; krishna Jana, Radha (International Journal of Computer Sciences and Engineering, 2026)
Disaster means a calamity which ruins the human civilization time to time at a bigger platform in many ways, it may be natural or it may be manmade, now days we are observing that almost all part of the world is suffering from CORONA a deadliest virus seems to be made by china as report and all countries corps are assuming or predicting the exact reason from year 2019 to till date. Above problem is the example of manmade disaster but apart from this we know the different types of disaster and their consequences in terms of loss in various ways. Its shows bad impact in almost all part of life from bottom to top as it influences life on all three platform i.e. socially, economically, and politically as a result peoples are start dying in lack of food and all various things which they need to survive their life on daily basis. Some of them will not only lose their family they will lose their shelter also by keeping all scenarios, Here we will try to build a completely different model which not only save the human life rather it will provides strength economically in such way that if happened such things then we all together can face any kind of problem and find a way to get out of it and also predict the future disaster in advance by applying Machine learning methods